Analisis Pengaruh Variabel Nilai TIU, TWK, Dan TKP Terhadap Kelulusan SKD Pada Tes CPNS Menggunakan Analisa Bivariat Sederhana - Andy Hermawan; Aji Saputra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to assess the impact of the General Intelligence Test (TIU), National Insight Test (TWK), and Personal Characteristics Test (TKP) on the success of the Basic Competency Selection (SKD) for Civil Servant Candidate (CPNS). Using data from participants in the Ministry of Law and Human Rights' SKD selection in 2023, we employed univariate analysis, simple bivariate analysis, and binning methods to comprehend variable relationships. Results reveal non-normal distributions for TIU, TWK, and TKP scores, highlighting the intricate nature of distribution in CPNS selection. While a positive correlation exists between variable values and total SKD score, binning analysis emphasizes TKP competitiveness over TIU and TWK scores. These findings offer practical insights for SKD participants to prepare effectively, with a focus on TIU, TWK, and TKP. Additionally, they contribute to transparency and effectiveness in the CPNS selection process. Further studies are recommended to explore additional factors, like age and gender, for the development of more holistic and accurate selection methods. This research supports enhancements in the adaptive and efficient CPNS SKD selection system.